Legal Certainty Regarding Home Care Medical Practices - Komang Tri Wahyu Utama; I Putu Gede Adiatmika; I Gusti Ayu Putri Kartika (GLOBAL HEALTH SCIENCE GROUP, 2026)
The practice of home care medicine in Indonesia has experienced rapid growth in line with the increasing demand for home-based health services. However, to date, there are no specific regulations that explicitly govern this practice within the national legal system. This study aims to analyze the legal vacuum surrounding home care and its implications for legal certainty, medical professional accountability, and patient protection. The method used is normative legal research with a legislative and conceptual approach, The data was obtained through the collection and analysis of legal materials, namely: primary legal materials (laws and regulations), secondary legal materials (research journals and books), and tertiary legal materials (legal dictionaries). The results of the study show that home care practices are carried out without a specific legal basis, thereby creating legal uncertainty and the potential for medical ethics violations. The absence of regulations also hinders the integration of these services into the JKN financing system and widens the gap in access to health services. The implications of these findings emphasize the urgency of formulating a comprehensive, adaptive, and inclusive regulatory framework to ensure the quality of home care services, protect patient rights, and strengthen the national health system. The designed regulations need to consider legal, ethical, technological, and social justice aspects in the implementation of home-based medical services.